Draft Annual Plan 1989-90 Vol. IV District Plan (Plain Area) Uttar Pradesh - Planning Commission (Planning Commission, 1989)
Apart from the removal of inter-district disparities, efforts are being made to reduce the intra-district disparities also. It has been specifically laid down in the guidelines that the new facilities to be created under the district plan will be located in the most backward block in that facility. A list of blocks according to descending order of availability of various facilities has been prepared at the district level for taking such locational decisions. A set pattern has emerged at the district level in allocation of district plan outlays. The major share is going towards building up of infrastructure and for fulfilling the minimum needs of the people in the district. Annexure shows the pattern of allocation of plan funds at the district level.
Government of Uttar Pradesh, Planning Department
Government of Uttar Pradesh